Heat Shock Protein 70 Inhibits Apoptosis in Cancer Cells Through Simultaneous and Independent Mechanisms - DUDEJA, VIKAS (2009)
BACKGROUND & AIMS: Heat shock proteins (HSPs) are highly conserved and serve a multitude of functions that mediate cell survival. HSP70, the only inducible form of the 70-kilodalton subfamily of HSPs, is overexpressed in pancreatic cancer cells and has been shown to inhibit caspase-dependent apoptosis. We aimed to elucidate the mechanism by which HSP70 inhibits apoptosis in cancer cells. METHODS: HSP70 expression was down-regulated in cultured pancreatic cancer cells by exposure to quercetin, triptolide, or short interfering RNAs. Intracellular Ca(2+), cytosolic cathepsin B activity, caspase-3 activity, cell viability, and lysosome integrity were measured using colorimetric assays. Immunofluorescence assays were used to localize cathepsin B and Lamp2. BAPTA-AM was used to chelate intracellular Ca(2+). RESULTS: Inhibition of HSP70 increased intracellular Ca(2+) levels in pancreatic and colon cancer cell lines and led to loss of lysosome integrity in pancreatic cancer cells. The release of intracellular Ca(2+) and lysosomal enzymes activated caspase-dependent apoptosis independently and simultaneously. CONCLUSIONS: HSP70 inhibits apoptosis in cancer cells by 2 mechanisms: attenuation of cytosolic calcium and stabilization of lysosomes. HSP70-mediated cell survival might occur in other types of cancer cells.